2016
DOI: 10.1681/asn.2016030278
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Slows Progression of Renal Function Decline Independently of Glycemic Effects

Abstract: Sodium-glucose cotransporter 2 inhibition with canagliflozin decreases HbA1c, body weight, BP, and albuminuria, implying that canagliflozin confers renoprotection. We determined whether canagliflozin decreases albuminuria and reduces renal function decline independently of its glycemic effects in a secondary analysis of a clinical trial in 1450 patients with type 2 diabetes receiving metformin and randomly assigned to either once-daily canagliflozin 100 mg, canagliflozin 300 mg, or glimepiride uptitrated to 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
221
1
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(255 citation statements)
references
References 22 publications
(27 reference statements)
23
221
1
10
Order By: Relevance
“…These data suggest that SGLT2i may have beneficial kidney effects, even in people with reduced kidney function, where glycemic benefits are limited (5). Interestingly, a recent study suggested that canagliflozin slows the progression of kidney function decline independently of effects on glycemia (6).…”
Section: Main Kidney Findings In the Published Clinical Trialsmentioning
confidence: 96%
See 1 more Smart Citation
“…These data suggest that SGLT2i may have beneficial kidney effects, even in people with reduced kidney function, where glycemic benefits are limited (5). Interestingly, a recent study suggested that canagliflozin slows the progression of kidney function decline independently of effects on glycemia (6).…”
Section: Main Kidney Findings In the Published Clinical Trialsmentioning
confidence: 96%
“…Finally, SGLT2i has been shown to slow the progression of kidney function decline independently of glycemic effects (6). Together with the unique mechanism of action of these drugs, which impact the kidney hemodynamics, this observation raises the hypothesis that their impact could also translate into improved kidney outcomes in nonpatients with diabetes.…”
Section: Knowledge Gaps and Future Studiesmentioning
confidence: 99%
“…In a study of 1450 T2DM patients on metformin randomly assigned to either canagliflozin or glimepiride, canagliflozin treated patients had significantly less decline in estimated glomerular filtration rate and greater reduction in urinary albuminto-creatinine ratio compared to glimepiride (47). The authors concluded that canagliflozin, compared with glimepiride, slowed the progression of renal disease over 2 years in patients with T2DM, and canagliflozin may confer renoprotective effects independently of its glycemic effects (47). This study was not designed nor powered to compare the renoprotective effects of canagliflozin versus glimepiride, so the results should be interpreted as hypothesis-generating (47).…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…It seems plausible that reabsorbed ascorbic acid protects renal proximal tubular cells from reactive oxygen species and exits the cells as dehydroascorbic acid, as indicated in the neurons [7]. Most recently, it has been demonstrated that SGTL 2 inhibitors slow progression of kidney disease in type 2 diabetes [8,9], where improvement of the bioavailability of vitamin C is not included in the putative mechanisms behind their renal effects. If this hypothesis is verified, SGLT2 inhibitors would be expected to have beneficial effects on the kidney still unknown beyond glucose lowering.…”
Section: Letter To Editormentioning
confidence: 99%